2015
DOI: 10.1186/s12889-015-1993-x
|View full text |Cite
|
Sign up to set email alerts
|

Is alcohol consumption in older adults associated with poor self-rated health? Cross-sectional and longitudinal analyses from the English Longitudinal Study of Ageing

Abstract: BackgroundIncreases in alcohol related mortality and morbidity have been reported among older people in England over the last decade. There is, however, evidence that drinking is protective for some health conditions. The validity of this evidence has been questioned due to residual confounding and selection bias. The aim of this study is to clarify which drinking profiles and other demographic characteristics are associated with poor self-rated health among a community-based sample of older adults in England.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 24 publications
5
30
0
1
Order By: Relevance
“…Positive self-perceived health was also associated with alcohol consumption among the long-lived elderly. Studies [25][26][27][28][29] have also observed an association between higher alcohol consumption and positive health perception, after adjustment for sociodemographic and lifestyle variables, corroborating the findings of this investigation. Other research showed that the prevalence of negative self-perceived health was higher among those who had stopped drinking, followed by individuals who did not drink 27 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Positive self-perceived health was also associated with alcohol consumption among the long-lived elderly. Studies [25][26][27][28][29] have also observed an association between higher alcohol consumption and positive health perception, after adjustment for sociodemographic and lifestyle variables, corroborating the findings of this investigation. Other research showed that the prevalence of negative self-perceived health was higher among those who had stopped drinking, followed by individuals who did not drink 27 .…”
Section: Discussionsupporting
confidence: 88%
“…Another point of discussion is that older people who consume alcohol do so because they are healthier, and this is the most likely explanation for the association found between alcohol and positive self-perceived health, in addition to social ties. It is also important to mention that there is a difference in the evaluation of alcohol consumption among the studies, since some studies evaluate low, moderate and high consumption 26 , some evaluate only moderate use 29,30 , some evaluate consumption doses 26,26,33 , and lastly, some evaluate frequency of consumption in days 26,33 , months 26 or years 27 , compared to individuals who have never consumed and/or individuals who stopped consuming alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus possible that alcohol fosters Extraversion over time through social factors connected with drinking. Moreover, alcohol drinkers relative to those who never drank or have stopped drinking tend to report a better health status (Frisher et al, ; see also Green & Polen, ), which in turn helps to maintain a more (socially) active lifestyle. Contrary to our expectation, however, moderate alcohol drinking was not significantly associated with change in Conscientiousness or Openness.…”
Section: Discussionmentioning
confidence: 99%
“…Most (27 / 33) respondents reported their consumption was consistent with the ‘lower risk’ weekly drinking benchmark (14 units or less for women, 21 units or less for men; Department of Health , Royal College of Psychiatrists ) commonly used by UK researchers when data were collected (Frisher et al . , Holmes et al . ).…”
Section: Methodsmentioning
confidence: 99%